Dietary patterns and birth outcomes in the ELSPAC pregnancy cohort. Issue 6 (17th December 2021) - Mikeš, Ondřej; Brantsæter, Anne Lise; Knutsen, Helle Katrine; Torheim, Liv Elin; Bienertová Vašků, Julie; Pruša, Tomáš; Čupr, Pavel; Janák, Karel; Dušek, Ladislav; Klánová, Jana
Abstract : Objectives: The aim of this study was to identify dietary patterns in a Czech pregnancy cohort established in the early postcommunist era and investigate associations between dietary patterns, maternal characteristics and birth outcomes. Methods: Pregnant women were recruited for the Czech part of the European Longitudinal Study of Pregnancy and Childhood. A self-reported questionnaire answered in late pregnancy was used to assess information about the weekly intake of 43 food items. Information about birth outcomes (birth weight, height, ponderal index, head circumference, cephalisation index, gestational length and Apgar score) was obtained from the National Registry of Newborns. Complete details on diet and birth outcomes were available for 4320 mother–infant pairs. Results and conclusion: The food items were aggregated into 28 variables and used for extraction of two dietary patterns by principal component factor analysis. The patterns were denoted 'unhealthy' and 'healthy/traditional' based on the food items with the highest factor loadings on each pattern. The 'unhealthy' pattern had high positive loadings on meat, processed food and confectionaries. In contrast, the 'healthy/traditional' pattern had high positive loadings on vegetables, dairy, fruits and wholemeal bread. Following adjustment for covariates, we found that high adherence to the unhealthy pattern (expressed as beta for 1 unit increase in pattern score), that is, the higher consumption of less healthy foods, was associated with lower birth weight: −23.8 g (95% CI −44.4 to −3.2) and length: −0.10 cm (95% CI −0.19 to −0.01) and increased cephalisation index: 0.91 μm/g (95% CI 0.23 to 1.60). The 'healthy/traditional' pattern was not associated with any birth outcomes. This study supports the recommendation to eat a healthy and balanced diet during pregnancy.